DEVELOPMENT OF ASTRO TIME ISLAMIC PRAYER SCHEDULE APPLICATION AND ALTITUDE CORRECTION TEST - Muhammad Jamaluddin (Al-Hilal: Journal of Islamic Astronomy, 2022)
The tool for calculating prayer times continues to develop. Likewise, there are several different formulas for calculating prayer times, both with the addition of altitude correction and without altitude correction. This article uses the prayer time formula which takes into account altitude corrections into an application called Islamic Astro Time which uses Matlab programming with solar data from the astronomical algorithms formula by Jean Meeus. This article is an experimental qualitative with descriptive analysis. This article finds that the calculation of prayer times in the Islamic Astro Time application using varying altitude levels results in different times. The difference in results starts from 2 minutes at a building height of 250 meters to more than 2 minutes depending on the level of height. The higher the position of the person praying, the greater the difference between the start of the prayer and the lower place. So that every Muslim who wants to pray must pay attention to the altitude correction factor with the sun's position approaching the horizon, namely the time of dawn, late dawn (ṭulū'), maghrib, and evening prayers.